The influence of track irregularities on the running behavior of high-speed trains. (January 2013) - Choi, I I-Yoon; Um, Ju-Hwan; Lee, Jun S; Choi, Hyun-Ho
Irregularities in railway tracks influence the running behavior of trains; large irregularities can result in poor ride comfort and in some cases derailment. Thus, it is important that the relationship between track irregularities and the running behavior of trains is identified and criteria for track irregularities are adequately established. However, the questions of how track irregularities affect the vehicle responses that determine running safety and ride comfort and how the wavelength and amplitude of each track irregularity influence the vehicle responses are barely addressed in the literature. This paper reports the results of computer simulation studies that were performed to investigate the influence of the longitudinal level, alignment and cross level of track irregularities on the running behavior of the 300 km/h KTX (Korea Train Express) train. A straight track was assumed in the calculations to ensure a focus on the effect of track irregularities. Track irregularities with various wavelengths and amplitudes were modeled using the VAMPIRE program; a vehicle dynamics modeling package that is widely utilized to study railway environments. Simulations on the effects of derailment coefficients, lateral loads, bogie acceleration and body acceleration created by track irregularities were performed to evaluate how the track irregularities affect the safety and ride comfort of the KTX. The results of the simulations indicate that track alignment has a significant impact on running safety whereas longitudinal level does not have any significant impacts.